Extent to which senior public relations managers influence strategic decision making in organisations. - Fun, Yip. (2008)
Excellent public relations is a critical factor in achieving organisational excellence. This study aims to provide insights on why some organisations achieve communication excellence while others do not by linking communication effectiveness with the power of the public relations department. Specifically, it examines the extent to which senior public relations practitioners influence strategic decision making in corporations, government agencies and non-profit organisations in Singapore. The findings of this study concluded that organisations in Singapore are still a distance from achieving communication excellence. Very few organisations see public relations as a tool to establish mutually beneficial relationships with key stakeholders. Senior public relations practitioners are generally excluded from management decision making, although they are empowered to make operational and tactical decisions relating to public relations.